The effect of iron oxide content on the structural and optical parameters of polyvinyl alcohol/graphene nanocomposite films. Issue 1 (28th December 2021) - Badawi, Ali; Alharthi, Sami S.; Althobaiti, Mohammed G.; Alharbi, Abdulaziz N.
Abstract: The effect of iron oxide nanoparticles (Fe2 O3 NPs) content on the structural and optical parameters of polyvinyl alcohol/graphene (PVA/G) blend has been investigated. Fe2 O3 NPs were synthesized by the hydrothermal procedure. Nanocomposite (NC) films of PVA/G filled with different amounts of Fe2 O3 NPs were equipped using the solution casting technique. The surface morphology, structural, and optical properties were examined by scanning electron microscope (SEM), X‐ray diffraction (XRD), and ultraviolet‐visible‐near‐IR (UV‐Vis‐NIR) spectrophotometry techniques, respectively. SEM micrographs reveal the homogenous distribution of Fe2 O3 NPs in the PVA/G matrix. The XRD analysis exhibits the formulation of the hematite phase of Fe2 O3 NPs and the semi‐crystalline nature of PVA/G NC films. The UV‐Vis‐NIR data analysis shows that the optical properties of the PVA/G blend could be tailored via Fe2 O3 NPs filling. Wemple–DiDomenico model is utilized to explore the dispersion parameters of the prepared NCs. A significant effect of Fe2 O3 NPs filling is realized on the oscillator and dispersion energies, infinite refractive index, dielectric constant, average oscillator strength and the lattice dielectric constant of the NC films. PVA/G filled Fe2 O3 NPs are suggested for different optical and storage applications.